Evaluating the thermal performance of the building envelope of condominiums in Davao City - Romuga, Vera Philina M. (2020)
This study aims to evaluate and analyze the thermal performance of the building envelopes of mid-rise and high-rise residential condominiums in Davao city. The researcher used the Residential Envelope Transmittance Value (RETV) formula by the Building and Construction in Singapore to determine the building?s thermal transmittance. Certain parameters were required to measure its RETV such as the window-to-wall ratio, solar heat gain coefficient, u-value of thermal transmittance, and shading coefficient of the fenestration. Solutions were also applied on the condominiums to lessen its initial value of thermal transmittance. According to the requirements of the RETV, the building must not exceed 25 W/m2 for it to be energy-efficient. The researcher studied 10 mid-rise and high-rise residential buildings in Davao city to be able to compare and analyze how different variables affect the RETV of the building. These variables include the shading devices of the fenestration, the window-to-wall ratio of the building, the materials of the building envelope, and the orientation of the building. This study proves that consideration of these variables and other different strategies are effective in having a sustainable design on the building envelopes for future developments.